The optimization of electro-discharge machining through topographic characterization - Ratna Aireen Rahmat (2008)
This project will attempt to investigate the electro discharge machining process through the characterization of the surface topography generated on different workpiece surfaces. It seeks to find out their similarity and differences through different operating parameter and topographical characteristic of the surface produced. The workpiece surface can be considered as “fingerprint” to the manufacturing process and can provide information about the influence of voltage, current, electrode tip, polarity and material. Through the advanced characterisation and analysis of the surface it is hoped that any change in these parameters can be detected.